Assessment of soil and water resources in the Gando Protected Area - jalil Badamfirooz; leyla sharifi (تحقیقات کاربردی علوم جغرافیایی)
By assessing the functions and ecosystem services of protected areas, planners and decision-makers of land use planning and sustainable development at the regional and national levels can be of great help. The present study specifically assesses the water and soil resources in the Gandu Protected Area and the economic valuation of these services. In order to model the ecosystem services of water balance, soil conservation and water quality, the hydrological model based on WWPSS remote sensing data was used. The simulation was carried out using a series of one-degree square mosaic images (one hectare) on a monthly scale. The Invest model and the replacement cost method were also used for economic valuation. The results showed that the total water produced in this area is 401,205,344 cubic meters per year. Also, the minimum, maximum and average water budgets are all negative and are equal to -1492.76, -38.04 and -639.24 mm per year respectively, which indicates a lack of rainfall and intense evaporation and transpiration in this region. The average potential pollution of surface water is 4.5% and this region prevents 2 tons per hectare of soil erosion annually. The real economic value of water production and soil conservation is estimated to be 20.18%, 67.54 and 2729.65 billion rials in 2019, respectively, with inflation correction. Three scenarios with discount rates (compound) of 8, 12 and 15% were used in the periods of 5, 10, 15 and 30 years to determine the economic value of the functions of these resources in the future. The results showed that, for example; With a discount rate of 15% and over a period of 30 years, the economic value of the water production and soil conservation functions reaches 4471.82 and 180730.13 billion rials, respectively. In total, the economic value of the water production and soil conservation functions is 0.35 and 14.17 percent of the total value of the region.